Medical Data Processing and Analysis (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The second edition of the Special Issue “Medical Data Processing and Analysis” highlights groundbreaking advancements in leveraging AI, ML, and emerging technologies for healthcare. Studies showcase innovative methods for enhancing diagnostic accuracy, such as explainable AI for autism detection, Pap smear analysis for cervical cancer, and retinal image segmentation for ocular conditions. Novel frameworks for medical image retrieval, disease detection using edge computing, and despeckling methods improve imaging precision and reliability. Hybrid models integrating blockchain, the IoT, and big data are proposed for monitoring infectious diseases, while assessments of interactive visualization tools such as BoldBI enhance trustworthiness in healthcare analytics. These contributions demonstrate how data-driven technologies can revolutionize early diagnosis, personalized treatment, and global health strategies.